The past and letters: Historical and literary representations of the province of Limón, Costa Rica (1900-1960) - Pacheco Calderón, Daniela (Revista de historia., 2024)
This article analyzes the historical and literary representations in the novels Murámonos, Federico by Joaquín Gutiérrez Mangel and Limón Blues by Anacristina Rossi, set in the banana plantations of Costa Rica in the first six decades of the 20th century. The narrative provided by the works was supported by primary documentation, especially local newspapers and testimonies of the time, which provided greater contextualization, interpretation and breadth to the topic. The research seeks to highlight the viability of using literature as a pedagogical tool in teaching History, integrating variables related to the literary landscape, daily life and social groups that were reflected in both novels. Likewise, the study encourages critical analysis, innovation in discursive expressions and strengthening literary interpretation from a historical point of view.